Screening of potential diatoms from shrimp pond with quorum quenching properties - Chui, Yu Ning (2018)
Quorum sensing is a mechanism which bacterial cell to cell communication that regulates the expression of various genes including virulence genes. In this study, the samples of diatoms are Strain BPD1, Amphora sp., Halamphora sp., Chaetoceros sp. and Thalassiosira sp. The quorum quenching properties from different diatom species were screened using reporter strain Chromobacterium violaceum CV026. The diameter of the inhibition zone were measured to identify the most active quorum quenching diatom. The unidentified diatom was extracted using 18S rRNA analysis and identified as Denticula sp. From 2 out of 5 diatoms, Denticula sp. and Amphora sp. showing as active quorum quenchers. The most active is Denticula sp. as it can inhibit the reporter strain CV026 in lower concentrations compare to Amphora sp. In this study, it showed that the diatoms with quorum quenching properties can be used as disease control in shrimp aquaculture.